Representation of Hunters in Kit Carson Short Story by Patricia Hill: A Transitivity Analysis - Eka Wahyu Nugrahani; Qanitah Masyquroh (Jurnal Ragam Pengabdian, 2026)
This research analyzes the representation of hunter characters, namely Kit and Tom, in Patricia Hill's short story "Kit Carson." Transitivity analysis from M.A.K. Halliday's (2004) within perspective of Systemic Functional Linguistics (SFL) was employed with a qualitative descriptive approach. The results indicate that Material Processes are the most prominent (45.15%), portraying the hunters through physical actions that highlight their bravery, strength, resilience, and initiative. Verbal Processes rank second (30.97%), underscoring the importance of communication in their planning and interactions. Furthermore, Mental Processes (12.39%) and Relational Processes (9.73%) also contribute to depicting their inner thoughts, feelings, and identities. Kit emerges as a highly active leader (frequently acting as Actor and Sayer), supported by Tom, who is also communicative and collaborative. In essence, the hunters in this story are rich and diverse characters: not only physically tough, but also dynamic, astute in communication, judicious in action, responsible, and principled. Kit embodies bravery and dominance, while Tom demonstrates calmness and loyalty.